ZNACZENIE KODEKSU KARNEGO Z 1932 R. DLA ROZWOJU NAUKI I PRAWA KARNEGO W POLSCE W XX WIEKU - Koredczuk, Józef (Zeszyty Prawnicze, 2016)
THE SIGNIFICANCE OF THE POLISH PENAL CODE OF 1932 FOR THE CRIMINAL LAW AND ACADEMIC EDUCATION DEVELOPMENT IN POLAND IN THE 20TH CENTURY Summary Since the year of 1932 marking the publication date of The Polish Penal Code also known as “Makarewicz Code”, there were strong indications that it would have a profound impact on the advancement in the field of Polish penal law and the academic-scientific area. Drawing from the highest standards and greatest solutions in Europe (i.e. The Code of Switzerland), The Polish Penal Code immediately gained substantial recognition abroad. Following World War II, it became an integral part of the socialist penal law system governing Poland at that time in history. Despite the numerous attacks it was exposed to, The Code served as an academic tool for educating many generations of lawyers and until 1969 it remained a main source book for law studies lectures. Additionally, it was considered to be a synonym of well-founded and stable Polish law and was applied as a benchmark for codification works in Poland dating back to 1969 and 1997. Having regard to the declarations presented by classical and sociological school with its reference to the penal law education, The Penal Code of 1932 had a great influence on the evolution of Polish academic education and criminal law in Poland of 20th century. Today this statement is reinforced by the fact that its author – Juliusz Makarewicz is regarded as the most prominent penal law professor. The Makarewicz Code is not only recognized as an outstanding judiciary achievement but also as a valuable academic-scientific point of reference. It is a symbol of the finest traditions in Polish law associated with progress, innovation and the one that elaborates on institutions that secure and attest to obeying the penal law regardless of the political roles it may play.